KESEJAHTERAAN PSIKOLOGIS REMAJA KORBAN BULYYING PONDOK PESANTREN : BAGAIMANA PERAN PEER SUPPORT? indonesia - Afriliani, Rindi; Subaidi (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study was conducted to determine the extent to which peer support influences the psychological well-being of adolescent victims of bullying in Islamic boarding schools. Adolescents who experience bullying in Islamic boarding schools continuously will cause a decrease in the level of psychological well-being which results in a person not having good communication with their environment. In this study there were 150 respondents with an age range of 13-15 years who were taken based on certain criteria using purposive sampling techniques. This study used a simple regression analysis technique with the help of JASP 0.19.3.0 software. The results of the study showed a correlation coefficient (R) of 0.539 with a calculated F of 80.251 and a significance level of 0.001 (p <.001) meaning that there is a significant positive relationship between peer support and the psychological well-being of adolescent victims of bullying in Islamic boarding schools where the peer support variable provides an effective contribution of 35.2% to the psychological well-being variable.